PEMBERDAYAAN MASYARAKAT PEDESAAN DENGAN ALAT GEOFISIKA: DETEKSI AIR TANAH DI DESA LAM APENG, ACEH - Darisma, Dian; Salma Salsabila, Rifa; Tarmizi; Amsir; Asrillah; Idris, Syafrizal; Tri Anda, Sabrian; Sapta Wirandha, Freddy (Fakultas Teknik, Universitas Samudra, 2025)
This community service program aims to map zones that have the potential to have aquifer layers as sources of clean water. The activity was carried out in Lam Apeng Village, Aceh Province. Clean water is a basic human need in life and in this village getting sufficient water sources or aquifers is still a challenge. By using the geophysical method, namely the geoelectric method, which is one of the geophysical methods widely used in Indonesia as an environmentally friendly and inexpensive method, we can identify underground layers that contain water based on the resistivity values ​​obtained from the measurements. Community involvement in data collection can also help with general mapping in the research area. The survey results show a potential aquifer zone at a depth of 6 to 18 meters. These findings can support future well drilling efforts. This activity shows the importance of combining science and local participation to solve everyday problems in rural areas.